2021
DOI: 10.1021/acs.jpcb.1c03107
|View full text |Cite
|
Sign up to set email alerts
|

Hydration and Seamless Integration of Hydrogen Peroxide in Water

Abstract: Raman multivariate curve resolution is used to decompose the vibrational spectra of aqueous hydrogen peroxide (H2O2) into pure water, dilute H2O2, and concentrated H2O2 spectral components. The dilute spectra reveal four sub-bands in the OH stretch region, assigned to the OH stretch and Fermi resonant bend overtone of H2O2, and two nonequivalent OH groups on water molecules that donate a hydrogen bond to H2O2. At high concentrations, a spectral component resembling pure H2O2 emerges. Our results further demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…28 Nevertheless, studies of H 2 O 2 − H 2 O solutions have generally concluded that these solutions are close to ideal, at least in the liquid state. 6,28 The modest value of hydrogen peroxide's standard adsorption free energy is certainly consistent with these other properties.…”
Section: ■ Results and Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…28 Nevertheless, studies of H 2 O 2 − H 2 O solutions have generally concluded that these solutions are close to ideal, at least in the liquid state. 6,28 The modest value of hydrogen peroxide's standard adsorption free energy is certainly consistent with these other properties.…”
Section: ■ Results and Discussionmentioning
confidence: 63%
“…As discussed above, the GARS probe depth is expected to be considerably deeper than the upper 5−10 A in the surface region, most likely exploring the same depth profile as surface tension measurements. The "seamless integration" of H 2 O 2 into the water structure, 6 due to From the slope and intercept, the kinetic equilibrium constant is obtained. (b) Plot of the data, fit using eq 4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthracene is seen to exist in clumps at the interface, rather than being evenly distributed there, covering only 7% of the surface at amounts that would nominally form a monolayer . The observation that there is not significant fluorescence quenching of pyrene by hydrogen peroxide at the ice surface further suggests that the highly soluble hydrogen peroxideexpected to be homogeneously distributed at the interfaceis not in effective contact with the much less soluble pyrene. Hydrogen peroxide shows only a very mild freeze-concentration effect, suggesting that this highly soluble species is evenly incorporated into the ice and liquid portions.…”
Section: Discussionmentioning
confidence: 94%